Evaluasi Alinemen Vertikal Terhadap Kecelakaan Lalu Lintas Melalui Pendekatan EAN dan UCL - Moch Farhan; Ida Farida (Institut Teknologi Garut, 2026)
Traffic accidents that frequently occur on the Patrol-Kamojang road section in Bandung Regency indicate a high safety risk due to the incompatibility of geometric conditions, particularly vertical alignment, with applicable technical standards. This study aims to analyze the characteristics of vertical alignment on this section, assess its effect on accident rates, and provide recommendations for improvement. Primary data was obtained through field surveys in the form of measurements of elevation, segment length, and slope using a theodolite, measuring rod, and tape measure. Secondary data consisted of a recapitulation of accidents from 2022 to 2024 from the police, including the frequency, location, and type of accidents. The analysis was conducted by comparing the geometric data with Bina Marga standards, calculating the accident rate using the Equivalent Accident Number (EAN), and setting the Upper Control Limit (UCL) for blackspot identification. In addition, the critical length and geometric adjustment requirements were calculated as the basis for technical recommendations. The results of the study show that several segments have a slope of up to 33.84%, exceeding the safety limit and correlating with an above-average EAN value and exceeding the UCL, thus being designated as priority blackspots. This study identifies accident-prone locations and recommends vertical alignment improvements, and can be used as a reference for relevant agencies in improving traffic safety on hilly roads.